Effects of cigarette smoke on killer cell activation in chronic obstructive pulmonary disease - Wang, Jia (2015)
Chronic Obstructive Pulmonary Disease (COPD) is a chronic inflammatory disease involving both innate and adaptive immune responses. Abnormal numbers of inflammatory cells have been examined in COPD subjects, as well as the effects of cigarette smoking on immune cells and molecules. Killer cells, including CD8+ T cells, NKT-like cells and NK cells, are thought to play a role in the development of COPD through their cytotoxic functions. In this project, we report ex vivo, activation levels of these cell types in COPD patients, as well as effects induced by cigarette smoke extract in vitro.